2020
DOI: 10.1002/brb3.1726
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pentadecapeptide BPC 157 on hippocampal ischemia/reperfusion injuries in rats

Abstract: Background and purpose We focused on the, yet undescribed, therapy effect of the stable gastric pentadecapeptide BPC 157 in hippocampal ischemia/reperfusion injuries, after bilateral clamping of the common carotid arteries in rats. The background is the proven therapy effect of BPC 157 in ischemia/reperfusion injuries in different tissues. Furthermore, there is the subsequent oxidative stress counteraction, particularly when given during reperfusion. The recovering effect it has on occluded vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
222
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(324 citation statements)
references
References 86 publications
(295 reference statements)
9
222
0
Order By: Relevance
“…Therefore, stable gastric pentadecapeptide BPC 157 is effective in wound healing (Seiwerth et al, 1997;Mikus et al, 2001;Sikiric et al, 2003;Xue et al, 2004a;Bilic et al, 2005;Seveljevic-Jaran et al, 2006;Tkalcevic et al, 2007;Huang et al, 2015), much like it is effective also in counteracting bleeding disorders (Stupnisek et al, 2012;Stupnisek et al, 2015;Vukojevic et al, 2018), produced by amputation, and/or anti-coagulants application, or major vessel occlusion, along with the evidence that pentadecapeptide BPC 157 may prevent and/or attenuate or eliminate, thus, counteracting both arterial thrombosis (Hrelec et al, 2009;Gojkovic et al, 2020;Kolovrat et al, 2020) and venous thrombosis (Vukojevic et al, 2018;Gojkovic et al, 2020;Kolovrat et al, 2020). Consequently, the therapy signifies the recovering effect BPC 157 has on occluded vessels (Vukojevic et al, 2018;Gojkovic et al, 2020;Kolovrat et al, 2020;Vukojevic et al, 2020), bypassing the occlusion (Duzel et al, 2017;Amic et al, 2018;Drmic et al, 2018;Vukojevic et al, 2018;Gojkovic et al, 2020;Kolovrat et al, 2020;Vukojevic et al, 2020), appears as the specific effect of BPC 157 in ischemia/reperfusion (Duzel et al, 2017;Amic et al, 2018;Drmic et al, 2018;Vukojevic et al, 2018;Gojkovic et al, 2020;Kolovrat et al, 2020;…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, stable gastric pentadecapeptide BPC 157 is effective in wound healing (Seiwerth et al, 1997;Mikus et al, 2001;Sikiric et al, 2003;Xue et al, 2004a;Bilic et al, 2005;Seveljevic-Jaran et al, 2006;Tkalcevic et al, 2007;Huang et al, 2015), much like it is effective also in counteracting bleeding disorders (Stupnisek et al, 2012;Stupnisek et al, 2015;Vukojevic et al, 2018), produced by amputation, and/or anti-coagulants application, or major vessel occlusion, along with the evidence that pentadecapeptide BPC 157 may prevent and/or attenuate or eliminate, thus, counteracting both arterial thrombosis (Hrelec et al, 2009;Gojkovic et al, 2020;Kolovrat et al, 2020) and venous thrombosis (Vukojevic et al, 2018;Gojkovic et al, 2020;Kolovrat et al, 2020). Consequently, the therapy signifies the recovering effect BPC 157 has on occluded vessels (Vukojevic et al, 2018;Gojkovic et al, 2020;Kolovrat et al, 2020;Vukojevic et al, 2020), bypassing the occlusion (Duzel et al, 2017;Amic et al, 2018;Drmic et al, 2018;Vukojevic et al, 2018;Gojkovic et al, 2020;Kolovrat et al, 2020;Vukojevic et al, 2020), appears as the specific effect of BPC 157 in ischemia/reperfusion (Duzel et al, 2017;Amic et al, 2018;Drmic et al, 2018;Vukojevic et al, 2018;Gojkovic et al, 2020;Kolovrat et al, 2020;…”
Section: Discussionmentioning
confidence: 99%
“…Besides, BPC 157 therapy effect always exhibited the functional recovery as well. This was noted with peripheral nerve injury ( Gjurasin et al, 2010 ) and central nervous disturbances (i.e., traumatic brain injury ( Tudor et al, 2010 ), various encephalopathies ( Ilic et al, 2009 ; Ilic et al, 2010 ; Ilic et al, 2011a ; Ilic et al, 2011b ; Klicek et al, 2013 ; Lojo et al, 2016 ; Drmic et al, 2017 ; Medvidovic-Grubisic et al, 2017 ), stroke ( Vukojevic et al, 2020 ), and spinal cord injury ( Perovic et al, 2019 )). Likewise, there are many functional and structural similarities between the retina and brain ( Osborne et al, 2004 ), and BPC 157 can likely cross the blood–brain barrier to induce neurotransmitter release ( Tohyama et al, 2004 ; Sikiric et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This particular point supports the recent evidence that vasomotor tone is carried out through BPC 157–specific activation of the Src-Caveolin-1-endothelial NOS (eNOS) pathway ( Hsieh et al, 1997 ). Likewise, BPC 157 has a modulatory role ( Sikiric et al, 2014 ) (in particular, to the blood pressure ( Sikiric et al, 1997 ) and thrombocytes function maintenance ( Stupnisek et al, 2012 , 2015 ; Konosic et al, 2019 )) and additional interaction with several molecular pathways ( Tkalcevic et al, 2007 ; Chang et al, 2011 , 2014 ; Hsieh et al, 2017 ; 2020; Kang et al, 2018 ; Vukojevic et al, 2018 ; Vukojevic et al, 2020 ; Park et al, 2020 ; Wu et al, 2020 ) [i.e., activation of the VEGFR2-Akt-eNOS signaling pathway without the need of other known ligands or shear stress ( Hsieh et al, 2017 )]. To illustrate its modulatory role on NO-system functions ( Sikiric et al, 2014 ), BPC 157 may counteract L-NAME hypertension and pro-thrombotic effect as well as L-arginine hypotension and antithrombotic effect ( Sikiric et al, 1997 ; Stupnisek et al, 2015 ), and induce its own NO-release ( Sikiric et al, 1997 ; Turkovic et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous papers have reported that stable gastric pentadecapeptide BPC 157 can regulate angiogenesis during the healing process by rescuing the duodenal lesions in rats through interacting with the nitric oxide (NO) system and reducing of free radical formation, 14 and also can resolve pringle maneuver 15 and hippocampal ischemic damage in rats due to ischemia or reperfusion. 16 Its strong angiogenic effect is mainly via activation of the VEGF-AKT-eNOS signaling pathway. 17 Furthermore, BPC 157 has also been demonstrated to promote vascular endothelial and tendon cell proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%